Alteration in DNA-binding affinity of Wilms tumor 1 protein due to WT1 genetic variants associated with steroid - resistant nephrotic syndrome in children - Martin Bezdicka; Filip Kaufman; Ivana Krizova; Alzbeta Dostalkova; Michaela Rumlova; Tomas Seeman; Karel Vondrak; Filip Fencl; Jakub Zieg; Ondrej Soucek (Scientific Reports, 2022)
Abstract Approximately one third of children with steroid-resistant nephrotic syndrome (SRNS) carry pathogenic variants in one of the many associated genes. The WT1 gene coding for the WT1 transcription factor is among the most frequently affected genes. Cases from the Czech national SRNS database were sequenced for exons 8 and 9 of the WT1 gene. Eight distinct exonic WT1 variants in nine children were found. Three children presented with isolated SRNS, while the other six manifested with additional features. To analyze the impact of WT1 genetic variants, wild type and mutant WT1 proteins were prepared and the DNA-binding affinity of these proteins to the target EGR1 sequence was measured by microscale thermophoresis. Three WT1 mutants showed significantly decreased DNA-binding affinity (p.Arg439Pro, p.His450Arg and p.Arg463Ter), another three mutants showed significantly increased binding affinity (p.Gln447Pro, p.Asp469Asn and p.His474Arg), and the two remaining mutants (p.Cys433Tyr and p.Arg467Trp) showed no change of DNA-binding affinity. The protein products of WT1 pathogenic variants had variable DNA-binding affinity, and no clear correlation with the clinical symptoms of the patients. Further research is needed to clarify the mechanisms of action of the distinct WT1 mutants; this could potentially lead to individualized treatment of a so far unfavourable disease.